2018
DOI: 10.1186/s10194-018-0945-0
|View full text |Cite
|
Sign up to set email alerts
|

Post-concussion syndrome among patients experiencing head injury attending emergency department of Hawassa University Comprehensive specialized hospital, Hawassa, southern Ethiopia

Abstract: IntroductionPost-concussion syndrome (PCS) is defined as the presence of 3 or more of the following signs and symptoms after experiencing head injury such as headache, dizziness, fatigue, irritability, insomnia, difficulty of concentration or memory difficulty. In Ethiopia, even though there was no research conducted on post-concussion syndrome, it is common health problems after experiencing head trauma that affect the productive age group, which directly or indirectly influences the development of the countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…Socio-demographic characteristic such as age and sex were not significantly associated with PCS following MTBI. This present study is in line with other previous studies conducted in Ethiopia and America (9,15) . This finding indicated that there was no effect on PCS symptoms of some demographic data from the subjects.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Socio-demographic characteristic such as age and sex were not significantly associated with PCS following MTBI. This present study is in line with other previous studies conducted in Ethiopia and America (9,15) . This finding indicated that there was no effect on PCS symptoms of some demographic data from the subjects.…”
Section: Discussionsupporting
confidence: 94%
“…This current study showed that headache and being irritable symptoms are the most common dangerous symptoms that patients need to be cautious because it has been the main leading causes of patients into the severity following MTBI. This study is consistent with a study conducted in Hawassa city Ethiopia (9) . The most frequently occurring symptoms of PCS following MTBI were headache, being irritable, and forgetfulness.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Secondary injury starts from this primary injury and emerges hours, days, or months later, involves various events such as oxidative stress, modified calcium homeostasis, inflammation, and axonal damage, terminating in cellular degeneration, disturbed neural circuits, and impaired synaptic transmission and synaptic plasticity [6]. Behaviorally, these alterations manifest as post traumatic headache, depression, individuality changes, anxiety, aggression, and deficits in attentiveness, cognition, sensory processing, and communication [7][8][9].…”
Section: The Pathophysiology Of Tbimentioning
confidence: 99%
“…Thankfully, 80% of TBIs are mild and leave subjects with minor or no cerebral damage. Nonetheless, the consequences of mild TBIs (mTBI) are often characterized by a broad array of somatosensory and cognitive symptoms, called post-traumatic syndrome, which tend to be overlooked by the public as a whole, despite causing vast medical and socioeconomic problems worldwide [3,4], hence the term ''silent public health epidemic''.…”
mentioning
confidence: 99%